1985
DOI: 10.1037/0021-843x.94.3.243
|View full text |Cite
|
Sign up to set email alerts
|

The dissociation of an experience: The hidden observer observed.

Abstract: Studies of the "hidden observer" phenomenon (Hilgard, 1977) have been vulnerable to criticism because of a number of methodological weaknesses. In the present study, a modified procedure was used with I 1 subjects, in an attempt to correct for some of these deficiencies. The critical modifications were that no prior practice in dissociation was given before the hidden observer was assessed, the notion of hidden information was introduced only after the stimulus was no longer present, and independently verifiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Once discovered, the hidden observer phenomenon was investigated extensively in Hilgard's laboratory and others. Hidden observers were obtained in association with hypnotic suggestions for analgesia to experimental pain (Hilgard, 1973a; Hilgard, Hilgard, Macdonald, Morgan, & Johnson, 1978; Hilgard, Morgan, & Macdonald, 1975; Knox, Morgan, & Hilgard, 1974), deafness (Crawford, Macdonald, & Hilgard, 1979), and negative hallucinations (i.e., not seeing something that is there; Zamansky & Bartis, 1985). The basic paradigm of these studies is to select participants who have demonstrated high levels of responsiveness to suggestion, tell them that there is (or may be) a hidden part of them that is more aware than their hypnotized part, establish a cue for communicating with the hypnotized part, administer a difficult hypnotic suggestion, and assess the effect of the suggestion with and without the hidden observer cue.…”
Section: The Empirical Basementioning
confidence: 99%
See 1 more Smart Citation
“…Once discovered, the hidden observer phenomenon was investigated extensively in Hilgard's laboratory and others. Hidden observers were obtained in association with hypnotic suggestions for analgesia to experimental pain (Hilgard, 1973a; Hilgard, Hilgard, Macdonald, Morgan, & Johnson, 1978; Hilgard, Morgan, & Macdonald, 1975; Knox, Morgan, & Hilgard, 1974), deafness (Crawford, Macdonald, & Hilgard, 1979), and negative hallucinations (i.e., not seeing something that is there; Zamansky & Bartis, 1985). The basic paradigm of these studies is to select participants who have demonstrated high levels of responsiveness to suggestion, tell them that there is (or may be) a hidden part of them that is more aware than their hypnotized part, establish a cue for communicating with the hypnotized part, administer a difficult hypnotic suggestion, and assess the effect of the suggestion with and without the hidden observer cue.…”
Section: The Empirical Basementioning
confidence: 99%
“…Spanos, Flynn, and Gwynn (1988) demonstrated a similarly flexible hidden observer in conjunction with suggested negative hallucinations. Previously, Zamansky and Bartis (1985) had reported a study in which they had administered negative hallucination suggestions for participants to see a blank page when the page actually had a clearly visible number imprinted on it. Spanos et al found that all of the participants who had initially denied seeing the number on the page claimed that they had seen the number when the experimenter contacted their hidden observer.…”
Section: The Empirical Basementioning
confidence: 99%
“…For Hilgard, the hidden observer was only one example of dissociation in hypnosis: the stimulus is represented in the cognitive system, but in a manner not normally accessible to phenomenal awareness (Kihlstrom, 1984(Kihlstrom, , 1992(Kihlstrom, , 1998(Kihlstrom, , 2005a. Although Hilgard's observations of covert pain reports in analgesia have been repeated by other investigators and have been extended to deafness, dreams, anosmia and negative hallucination (Spanos and Hewitt, 1980;Laurence and Perry, 1981;Nogrady, McConkey, Laurence and Perry, 1983;Spanos, Gwynn and Stam, 1983;Zamansky and Bartis, 1985;Mare, Lynn, Kvaal, Segal and Sivec, 1994), interpretation of the phenomenon has been more controversial. Coe and Sarbin (1977) argued that hidden observer instructions merely gave subjects permission to report pain that they actually felt all along.…”
Section: Introductionmentioning
confidence: 92%
“…As pointed out by St. Jean, investigators labeled by Sutcliflfe (1961) as "credulous" (e.g. Zamansky & Bartis 1985) are inclined to believe such reports. According to them, the subjects did not consciously see the "18" at the time of presentation.…”
Section: Editorial Commentarymentioning
confidence: 99%